1993
DOI: 10.1093/oxfordjournals.annonc.a058622
|View full text |Cite
|
Sign up to set email alerts
|

Epirubicin and ifosfamide in advanced soft tissue sarcomas

Abstract: This combination proved to be feasible and tolerable. The overall response rate does not appear to be superior to those with other standard treatments, but it should be pointed out that our patient population was totally unselected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Imatinib is a potent inhibitor of KIT signaling tyrosine kinase inhibitor (5,6,10,20,29) . Before the use of imatinib, the median survival of the patients with resectable disease was 66 months (5,9) and 9 to 12 months in irresectable disease (3,4,9,11,12,14,38) .…”
Section: Introductionmentioning
confidence: 99%
“…Imatinib is a potent inhibitor of KIT signaling tyrosine kinase inhibitor (5,6,10,20,29) . Before the use of imatinib, the median survival of the patients with resectable disease was 66 months (5,9) and 9 to 12 months in irresectable disease (3,4,9,11,12,14,38) .…”
Section: Introductionmentioning
confidence: 99%
“…The anthracyclines doxorubicin and epirubicin (EPI), and the oxazaphosphorine analog of cyclophosphamide, ifosfamide (IFO), have been widely used in the front-line treatment of advanced sarcomas in view of their well known antitumor activity, and response rates up to 40% have been reported with the combination of them [1][2][3]. EPI doses in the range of 75-140 mg/m 2 every 3 weeks in combination with IFO doses in the range of 6-12 g/m2 have been adopted in concurrent administration schedules [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The objective response rate of 30% is clearly inferior to response rates reported from recent phase II studies with high dose ADM/IFO and comparable to the results of CYVADIC, standard-dose ADM/IFO or high-dose singleagent ADM [4,5,7,8,10,12,13,19], Hematological G-CSF was administered only in 8/35 patients with severe neutropenia. It was demonstrated that 7/8 patients could be referred to the next treatment cycle without toxicityrelated delay.…”
Section: Discussionmentioning
confidence: 43%
“…Metastatic soft tissue sarcoma requires systemic treat ment in the majority of patients, although single cases of successful salvage treatment by surgical metastasectomy are reported [3], A widely varying single-agent activity of 5-30% due to the heterogeneity of histological subtypes of soft tissue sarcoma in children and adults was reported for Adriamycin (ADM), ifosfamide (IFO), ctoposide, dacar bazine (DTIC) and cisplatin (DDP) [4][5][6][7][8]. Response rates were further improved using different combination che motherapy regimens [4-6, 8, 9], Combination IFO, ADM and DTIC resulted in a response rate of 49% including 10% complete remissions (CR) [10].…”
Section: Introductionmentioning
confidence: 99%